Interfacially Super‐Assembled Asymmetric and H2O2 Sensitive Multilayer‐Sandwich Magnetic Mesoporous Silica Nanomotors for Detecting and Removing Heavy Metal Ions. (18th March 2021) - Qiu, Beilei; Xie, Lei; Zeng, Jie; Liu, Tianyi; Yan, Miao; Zhou, Shan; Liang, Qirui; Tang, Jinyao; Liang, Kang; Kong, Biao
Abstract: Asymmetric hollow and magnetic mesoporous silica nanocomposites have great potential applications due to their unique structural–functional properties. Here, asymmetric multilayer‐sandwich magnetic mesoporous silica nanobottles (MMSNBs) are presented through an interfacial super‐assembly strategy. Asymmetric hollow silica nanobottles (SNBs) are first prepared, and Fe3 O4 nanoparticles monolayers and mesoporous silica layers are uniformly super‐assembled on the surfaces of SNBs, respectively. The high Fe3 O4 nanoparticles loading endows MMSNBs with a high magnetization (8.5 emu g −1 ), while the mesoporous silica layers exhibit high surface area (613.4 m 2 g −1 ) and large pore size (3.6 nm). MMSNBs can be employed as a novel type of enzyme‐powered nanomotors by integrating catalase (Cat‐MMSNBs), which show an average speed of 7.59 µm s −1 (≈25 body lengths s −1 ) at 1.5 wt% H2 O2 . Accordingly, the water quality can be monitored by evaluating the movement speed of Cat‐MMSNBs. Moreover, MMSNBs act as a good adsorbent for removing more than 90% of the heavy metal ions with the advantage of the mesoporous structure. In addition, the good magnetic response enables the MMSNBs with precise directional control and is conducive to recycling for repeated operation. This bottom‐up interfacial super‐assembly construction strategy allows for a new understanding of the rational design and synthesis of multi‐functional nanomotors. Abstract : Enzyme‐functionalized, asymmetric multilayer‐sandwich magnetic mesoporous silica nanobottle (MMSNB)‐like nanomotors are synthesized using a generalized interfacial super‐assembly strategy. The nanomotors demonstrate an effective heavy metal ion detection ability, while the mesoporous MMSNB frameworks display an excellent contaminant removal ability.